-(56x-12)=

Simple and best practice solution for -(56x-12)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(56x-12)= equation:


Simplifying
-1(56x + -12) = 0

Reorder the terms:
-1(-12 + 56x) = 0
(-12 * -1 + 56x * -1) = 0
(12 + -56x) = 0

Solving
12 + -56x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -56x = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -56x = 0 + -12
-56x = 0 + -12

Combine like terms: 0 + -12 = -12
-56x = -12

Divide each side by '-56'.
x = 0.2142857143

Simplifying
x = 0.2142857143

See similar equations:

| 6y-87=7y | | -3=14+x | | 5c-3=6c | | -64=6b-4 | | 2n-7=5n-10 | | 13-3(5x-4)=-2 | | 6x+48=8x+8 | | -4x-5x=27 | | -64=6b | | 1568/7.28=h | | -8u+3(u-4)=-22 | | 3x^2-12x+31=22 | | 4a-2=6a | | 3y-5=46 | | (5+x)(3+x)(x)= | | 4(x+8)-6=26 | | -2x-12=-6(x+4) | | -3x^2+30X+90=0 | | 3x=10+7x | | 3x-4=7+4 | | -9=36+6 | | 2y+y-3=6 | | -6t+18=30 | | -11x-1=87 | | 3x=7x-10 | | 1.24+5p= | | 4(v+3)-6u=18 | | p(x)=x^3-xfindp(5) | | 5a-6=3a+20 | | 3x+5(x-8)=4(x-5)-12 | | 49.5=9.h/2 | | y^2-y-5=y-2 |

Equations solver categories